2008
DOI: 10.2146/ajhp080013
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient medication history verification by pharmacy students

Abstract: Pharmacy students' participation in obtaining medication histories improved the completeness and accuracy of patient medication records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 4 publications
1
49
2
Order By: Relevance
“…Another study demonstrated that pharmacy students could perform accurate, thorough admission medication histories and identify and, under the supervision of the pharmacist preceptor, correct important omissions, thereby improving the completeness and accuracy of more than 67% of patient medication records. 21 Pharmacy students have also conducted medication reconciliation activities with patients admitted to an emergency department, finding one or more medications missing from the medication lists recorded at triage for nearly 50% of patients. 22 Although these studies illustrate that pharmacy students can be effective in conducting these activities while maximizing preceptor time, experiences involving students in transitional care at hospital discharge are lacking.…”
mentioning
confidence: 99%
“…Another study demonstrated that pharmacy students could perform accurate, thorough admission medication histories and identify and, under the supervision of the pharmacist preceptor, correct important omissions, thereby improving the completeness and accuracy of more than 67% of patient medication records. 21 Pharmacy students have also conducted medication reconciliation activities with patients admitted to an emergency department, finding one or more medications missing from the medication lists recorded at triage for nearly 50% of patients. 22 Although these studies illustrate that pharmacy students can be effective in conducting these activities while maximizing preceptor time, experiences involving students in transitional care at hospital discharge are lacking.…”
mentioning
confidence: 99%
“…To date, problems with the medication reconciliation process have largely been addressed at the system level, rather than the level of patient or caregiver, through varied interventions to make the process of obtaining a medication history more efficient and more effective. [4][5][6][7][9][10][11][12][13][14] Both patients and health care professionals discussed the importance of medication histories and their role in safe and effective health care. This importance was related not only to the use of medication histories in prescribing additional medications, but also their use as an aid in determining past medical histories and diagnoses and in identifying and preventing drug therapy problems.…”
Section: Discussionmentioning
confidence: 99%
“…18 It is noteworthy that not only are medication reconciliation services provided to these institutions by student pharmacists, but it is also a great learning opportunity for the students. 19 In addition, the use of student pharmacists in the provision of MRS can prevent medication discrepancy. Medication discrepancy is an important reason for hospital readmission, and two-thirds of readmissions occur within the first three months.…”
Section: Innovations In Pharmacymentioning
confidence: 99%